Perancangan Dan Implementasi Desain Arsitektur Cloud Yang Aman Untuk Sistem Stock Pada Halutime Thrift Shop - Gautama Wijaya; Franky Viky Franklyn (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Information technology is currently experiencing very fast development. Cloud computing is a new era in today's technological developments. Cloud computing is an information technology service where resources are taken from the internet through web-based tools and applications. One of the cloud computing is GCP (Google Cloud Platform) which is a collection of cloud computing services offered by Google. In this joural, we will design and implement a cloud architecture using GCP (Google Cloud Platform) and web server security using WAF (Web Application Firewall) for the stock system at Halutime Thrift Shop. Web Application Firewall (WAF) is a security concept that can be used to prevent various threats and attacks on web applications. This journal aims to provide an overview of the benefits for companies that use cloud computing technology. Cloud computing utilizes the internet as a virtual server center for the purpose of data maintenance and application services. The result of this activity is the design of a secure cloud architecture design using the ModSecurity application, for the stock system for Halutime Thrift Shop.